Cancer patients and the internet: a survey of the ‘quality of life’ working groups of the Arbeitsgemeinschaft für Internistische Onkologie and the Nord-Ostdeutsche Gesellschaft für Gynäkologische Onkologie - Gencer, Deniz; Tauchert, Felix; Müller-Keilhauer, Nina; Al-Batran, Salah-Eddin; Stahl, Michael; Oskay-Özcelik, Gülten; Hipp, Matthias; Leibbrand, Birgit; Prasnikar, Nicole; Trarbach, Tanja; Stoll, Christoph; van Kampen, Michael; et al. (Onkologie, 2011)
Background: Patient-reported outcomes, such as quality of life (QoL) assessment, are becoming more important as endpoint in clinical trials and for decision making regarding new anticancer product approvals. Nevertheless, numerous obstacles exist regarding the implementation of QoL assessment in the daily practice of medical oncologists. Regular, computerized or internet home-based QoL assessments could be a step forward. Methods: Using a 15-item paper questionnaire, we conducted a survey among 1580 cancer patients regarding their willingness to use internet QoL assessment, and collected personal data and information about current disease and performance status. Results: Younger patients (i.e. ≤65 years) significantly more often had internet access (78% versus 36%; χ2 test, p < 0.001). Moreover, the availability of internet access correlated with higher education levels. 55% of all polled patients are willing to use an internet-based QoL assessment tool, regardless of the type of internet access, whereas almost two-thirds (n = 600; 65%) of patients with their own internet access would be willing to use it for providing statements about QoL. Of these, especially younger patients in good health status with higher education degrees indicated their willingness to use such tools. Conclusion: These data may serve as a basis for identifying patient groups willing to participate in pilot projects to evaluate the implementation of internet-based regular assessment of QoL in cancer.